Edukasi KTR dan Deep Berithing Mencegah ISPA Untuk Mengurangi Risiko Stunting Di Desa Sukasari Kec.Air Periukan Kab.Seluma - Sari, Hartini Saputri Endang; Darmawansyah, Darmawansyah; Indriani, Vira Ardita; Agutina, Maya Diana (Utami Publisher, 2025)
Acute Respiratory Tract Infection (ARI) is one of the main causes of morbidity and mortality, especially in toddlers. In Seluma Regency, Bengkulu Province, the incidence of ARI is quite high, there are 22 cases of ARI, especially in the area of ​​Dusun 1, Sukasari Village which is affected by air pollution from industrial activities and cigarette smoke. The Thematic Community Service Program (KKN-T) of Dehasen University Bengkulu in 2025 focuses on efforts to prevent ARI through an educational approach, namely the ARI counseling method, the implementation of Smoke-Free Areas (KTR), the practice of deep breathing techniques, and the distribution of leaflets and Digital education. This activity was carried out through collaboration with village officials and the local community. The results of the activity showed an increase in public awareness regarding the importance of environmental cleanliness, reducing exposure to cigarette smoke, and the use of deep breathing techniques which aim to increase lung capacity and reduce the risk of respiratory tract infections with ARI symptoms. This program has proven effective as a community-based promotive and preventive strategy that can be a model for implementation in other areas. Cross-sector collaboration and ongoing education are essential to support efforts to reduce the incidence of ISPA, as well as contribute to preventing stunting by improving children's respiratory health.